Diurnal Measurements of Macular Thickness and Vessel Density on OCT Angiography in Healthy Eyes and Those With Ocular Hypertension and Glaucoma. Issue 10 (October 2020) - Milani, Paolo; Bochicchio, Sara; Urbini, Lara E.; Bulone, Ennio; Callegarin, Stefania; Pisano, Luca; Scotti, Lorenza; Zambon, Antonella; Bergamini, Fulvio
Abstract : Precis: Macular superficial capillary plexus (SCP) and thickness are reduced in eyes with glaucoma and ocular hypertension, but do not change significantly during the day. No relationships with age, intraocular pressure, systemic hypertension, or axial length were found. Purpose: The purpose of this study was to evaluate diurnal differences in retinal thickness and vessel density (VD) of the macular SCP and deep capillary plexus (DCP) using optical coherence tomography angiography among 3 groups: eyes with glaucoma, eyes with ocular hypertension, and healthy eyes. Methods: A consecutive series of individuals was recruited prospectively. Optical coherence tomography angiography was performed in the morning and in the evening. Results: Forty eyes from 23 individuals with glaucoma (58.35±6 y), 52 eyes from 32 individuals with ocular hypertension (58.84±7 y), and 73 eyes from 44 controls (57.84±6 y) were enrolled. Morning and evening measurements of all SCP-VD and retinal thickness parameters were statistically significantly different ( P <0.04) among the 3 groups of eyes. None of the DCP-VD parameters were significantly different. Daily changes in SCP-VD, DCP-VD, and retinal thickness among the groups of eyes were not statistically significant. Systemic hypertension, age, axial length, and diurnal changes in intraocular pressure were not significantly associated with diurnal fluctuations of SCP-VD, DCP-VD, or retinal thickness ( P >0.19). A positive linear correlation in diurnal changes was found between SCP-VD and DCP-VD in the fovea and in the parafovea ( r =0.5567 and 0.5892, respectively) and between SCP-VD and retinal thickness in the fovea and in the parafovea ( r =−0.2288 and 0.2418, respectively). Conclusions: Macular SCP-VD and thickness are reduced in eyes with glaucoma and ocular hypertension. Although diurnal changes in SCP-VD, DCP-VD and macular thickness were not significant among the groups, some linear correlations in increasing or decreasing values of the investigated parameters were found. Abstract : Supplemental Digital Content is available in the text.